Estudio sistemático del género Gouinia (Gramineae, Chloridoideae, Eragrostoideae) - Ortiz Diaz, Juan Javier (Instituto de Ecología, A.C., 1993)
A systematic treatment of the genus Gouinia is presented. Geographical distribution, morphology, leaf anatomy,  photosynthetic pathways and chromosome numbers are  analyzed. Twelve taxa of Gouinia, including 9 species and 6  varieties are recognized. One species, one variety and one  combination are new. Synonymy, descriptions, ecológica data,  discussions, common names and iists of herbarium specimens  are given for each species.